Clinical Judgment Revisited - Weed, L. L. (Methods of Information in Medicine, 1999)
It is widely recognised that accessing and processing medical information in libraries and patient records is a burden beyond the capacities of the physician’s unaided mind in the conditions of medical practice. Physicians are quite capable of tremendous intellectual feats but cannot possibly do it all. The way ahead requires the development of a framework in which the brilliant pieces of understanding are routinely assembled into a working unit of social machinery that is coherent and as error free as possible – a challenge in which we ourselves are among the working parts to be organized and brought under control.Such a framework of intellectual rigor and discipline in the practice of medicine can only be achieved if knowledge is embedded in tools; the system requiring the routine use of those tools in all decision making by both providers and patients.
Keywords: Decision Making; Knowledge Coupling; Clinical Judgment